Composite bismuth oxyhalide catalyst and preparation method thereof
By supporting molecular sieve, titanium dioxide, bismuth bromine oxide and active metal components in bismuth oxyhalide catalyst, and optimizing the preparation process and calcining conditions, the problem of low COD degradation efficiency of existing bismuth oxyhalide catalysts in wastewater treatment is solved, and a more efficient photocatalytic effect is achieved.
Patent Information
- Application Number
- CN202310946355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-07-28
AI Technical Summary
The application effect of existing bismuth oxyhalide catalysts in the field of photocatalytics has not been optimized, especially in sewage treatment, the efficiency of reducing COD in sewage is not high.
Through a specific preparation process, a composite bismuth oxyhalide catalyst is prepared, supported molecular sieve, titanium dioxide, bismuth bromine oxide and active metal components (such as Ag, Pd, Ru, Cu), and the performance of the catalyst is optimized through specific proportioning and calcining conditions.
The catalytic effect of the catalyst is significantly improved, especially in sewage treatment, which can effectively reduce COD in sewage and improve photocatalytic activity.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and more particularly to a composite bismuth oxyhalide catalyst and a preparation method thereof. Background Art
[0002] Bismuth oxyhalide is a V-VI-VII ternary layered semiconductor compound with a typical tetragonal skeleton structure (PbFCl type). The general structural formula can be represented by BiOX, where X can be I, Br, Cl and F. Bismuth oxyhalide is a loose layered structure, which is arranged in layers and has metastable properties. In each layer [Bi2O2] + The BiOX is connected to X(F, Cl, Br, I) by covalent bonds and maintained between layers by van der Waals forces. The structure of the entire bismuth oxyhalide is similar to the layered structure of graphite. Since the bond strength in the bismuth oxyhalide is very weak, the structure of the bismuth oxyhalide is easily deformed. Because of this characteristic of BiOX, its electron-hole pair separation efficiency is high and its application prospects in the field of photocatalysis are broad.
[0003] For example, it is used in clean energy conversion and environmental remediation, such as using photocatalysts to reduce CO2, decompose water to produce H2, treat wastewater, etc., which is both economical and environmentally friendly. Among many semiconductor materials, bismuth oxyhalide BiOX (X=Cl, Br, I) photocatalysts have unique electronic structures and good stability, and have attracted much attention in the field of photocatalysis. However, the effects of existing bismuth oxyhalide catalysts need to be further improved. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention proposes a composite bismuth oxyhalide catalyst and a preparation method thereof. The present invention prepares a composite bismuth oxyhalide catalyst loaded with active metal components through a specific preparation process and catalyst composition, and the catalyst has good catalytic effect.
[0005] One of the purposes of the present invention is to provide a composite bismuth oxyhalide catalyst, which comprises a molecular sieve; titanium dioxide, bismuth oxybromide and an active metal component supported on the molecular sieve;
[0006] The active metal component includes at least Ag.
[0007] In the catalyst of the present invention, preferably,
[0008] The molecular sieve is selected from at least one of mordenite and ZSM-5; preferably, the silicon-aluminum molar ratio of the mordenite molecular sieve is 10-50; the silicon-aluminum ratio of the ZSM-5 molecular sieve is 20-40; and / or,
[0009] The active metal component further includes at least one of Pd, Ru, and Cu.
[0010] The present invention finds that when Ag in the catalyst and at least one of Pd, Ru, and Cu are in a specific ratio, there is a good synergistic effect, which can further improve the catalytic effect of the catalyst. Preferably, the mass ratio of Pd to Ag is 0.3-0.5:1;
[0011] The mass ratio of Ru to Ag elements is 0.1-0.3:1;
[0012] The mass ratio of Cu to Ag elements is 0.4-0.6:1.
[0013] In the composite bismuth oxyhalide catalyst of the present invention, mordenite and ZSM-5 have a synergistic effect when used in a specific ratio, and can further improve the effect of the catalyst; preferably, the mass ratio of ZSM-5 to mordenite is 2-3:1.
[0014] In the catalyst of the present invention, preferably,
[0015] The mass ratio of titanium element to molecular sieve in titanium dioxide is 0.2~0.8:100;
[0016] The mass ratio of bismuth element to molecular sieve in bismuth oxybromide is 1-3:100;
[0017] The mass ratio of active metal component to molecular sieve is 0.01~0.08:100.
[0018] The second object of the present invention is to provide a method for preparing a composite bismuth oxyhalide catalyst, comprising the following steps:
[0019] (1) adding titanium tetrachloride dropwise into ice water to prepare a titanium source solution; adding molecular sieve into the titanium source solution for impregnation, separating the solid from the liquid, washing the solid, drying, and calcining once to obtain titanium dioxide / molecular sieve;
[0020] (2) dissolving sodium bismuthate in a mixed solvent of water and alcohol to obtain a bismuth salt solution, then adding titanium dioxide / molecular sieve for impregnation, then dropping hydrobromic acid under stirring, separating the solid and the liquid, washing the solid, and drying to obtain BiOBr / titanium dioxide / molecular sieve;
[0021] (3) BiOBr / titanium dioxide / molecular sieve and weak base are uniformly mixed in water, a solution containing an active metal component precursor is added to react, solid-liquid separation is performed, the solid is washed, dried, and calcined twice to obtain the composite bismuth oxyhalide catalyst.
[0022] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably, the following steps are included:
[0023] In step (1),
[0024] The concentration of titanium element in the titanium source solution is 0.5wt%-1.5wt%;
[0025] The mass ratio of the molecular sieve to the titanium element in the titanium source solution is 100:2-5;
[0026] The immersion temperature is 30-50°C and the immersion time is 1-1.5h;
[0027] The method of solid-liquid separation is centrifugal separation;
[0028] Wash 1-3 times; wash with water.
[0029] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably,
[0030] In step (1),
[0031] The drying temperature is 60-80°C; the drying time is 1-3 hours;
[0032] During the primary calcination, in a mixed atmosphere, the temperature is gradually increased from 60-80 degrees, and the temperature is increased to 250 degrees for heating for 10-30 minutes; the temperature is further increased to 300 degrees for heating for 25-40 minutes; the temperature is further increased to 400 degrees for heating for 25-35 minutes; the preferred temperature increase gradient is 5-15 degrees / minute; the preferred mixed atmosphere is a mixed atmosphere of argon and hydrogen, and the volume ratio of argon to hydrogen is 10:0.8-2.3.
[0033] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably,
[0034] In step (2),
[0035] The alcohol is selected from at least one of ethanol, methanol and propanol;
[0036] The volume ratio of water to alcohol is 1:1.5-3;
[0037] The concentration of bismuth element in the bismuth salt solution is 1wt%-5wt%;
[0038] The mass ratio of the molecular sieve and the bismuth element in the bismuth salt solution in step (1) is 100:1.5-4;
[0039] The concentration of hydrobromic acid is 30-50wt%;
[0040] The mass volume of the sodium bismuthate and hydrobromic acid is 1g: 9-12mL;
[0041] The method of solid-liquid separation is centrifugal separation;
[0042] The dripping time is 2-4h;
[0043] The number of washing times is 1-3 times; washing with water;
[0044] The drying temperature is 40-60°C and the drying time is 5-7 hours.
[0045] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably,
[0046] In step (2),
[0047] The drying temperature is 60-80°C; the drying time is 1-3 hours;
[0048] During the primary calcination, in a mixed atmosphere, the temperature is gradually increased from 60-80 degrees, and the temperature is increased to 250 degrees for 15-25 minutes; the temperature is further increased to 350 degrees for 45-60 minutes; the temperature is further increased to 450 degrees for 45-60 minutes; the preferred temperature increase gradient is 5-15 degrees / minute; the preferred mixed atmosphere is a mixed atmosphere of argon and hydrogen, and the volume ratio of argon to hydrogen is 10:1-3.
[0049] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably,
[0050] In step (3),
[0051] The weak base is selected from ammonium carbonate;
[0052] The active metal component precursor is selected from at least one of copper nitrate, palladium nitrate, ruthenium nitrate and silver nitrate.
[0053] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably,
[0054] In step (3),
[0055] The concentration of BiOBr / titanium dioxide / molecular sieve in water is 21-30 g / L;
[0056] The mass ratio of the molecular sieve to the metal component in the active metal component precursor in step (1) is 100:0.01-0.15;
[0057] The molar ratio of the weak base to the active metal component precursor is 1:1-1.2.
[0058] In the preparation method of the composite bismuth oxyhalide catalyst of the present invention, preferably,
[0059] In step (3),
[0060] The reaction time is 30-60 minutes;
[0061] The drying temperature is 50-60°C; the drying time is 1-2 hours;
[0062] The secondary calcination temperature is 200-250 degrees Celsius, the calcination time is 0.5-1.5 hours, and the calcination atmosphere is argon atmosphere.
[0063] The composite bismuth oxyhalide catalyst of the present invention is calcined once in a special atmosphere when loaded with titanium dioxide, which can optimize the surface defects / vacancies of titanium dioxide and is conducive to improving the effect of composite use with BiOBr. The present invention further loads active metals on BiOBr / titanium dioxide / molecular sieve, which can further improve the catalytic effect of the catalyst.
[0064] Compared with the prior art, the present invention has at least the following advantages:
[0065] The present invention prepares a catalyst of a composite bismuth oxyhalide catalyst loaded with an active metal component through a specific preparation process. The catalyst has a good catalytic effect and can be used in sewage treatment to effectively reduce COD in the sewage. DETAILED DESCRIPTION
[0066] The present invention is specifically described below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used for further explanation of the present invention. It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will no longer describe various possible combinations separately. In addition, various different embodiments of the present invention can also be combined arbitrarily, as long as they do not violate the idea of the present invention, and the technical solution thus formed belongs to a part of the original disclosure of this specification, and also falls into the protection scope of the present invention.
[0067] Example 1
[0068] A method for preparing a composite bismuth oxyhalide catalyst comprises the following steps:
[0069] (1) Add titanium tetrachloride dropwise into ice water to prepare a titanium source solution (the concentration of titanium element is 1 wt%); add molecular sieves (ZSM-5 and mordenite; the mass ratio of the two is 2:1; the silicon-aluminum molar ratio of the mordenite molecular sieve is 25; the silicon-aluminum ratio of the ZSM-5 molecular sieve is 28) into the titanium source solution for impregnation, and the mass ratio of the molecular sieve to the titanium element in the titanium source solution is 100:3; the impregnation temperature is 35°C, and the impregnation time is 1 hour; centrifugal separation, washing the solid with water for 3 times, drying at 80°C for 1 hour, and gradually increasing the temperature from 80°C to 250°C for 30 minutes in a mixed atmosphere of argon and hydrogen (the volume ratio of argon and hydrogen is 10:1); continue to increase the temperature to 300°C and heat for 25 minutes; continue to increase the temperature to 400°C and heat for 35 minutes; the temperature increase gradient is 15°C / minute to obtain titanium dioxide / molecular sieve;
[0070] (2) dissolving sodium bismuthate in a mixed solvent of water and alcohol (ethanol) (the volume ratio of water to alcohol is 1:2) to obtain a bismuth salt solution (4 wt%), then adding titanium dioxide / molecular sieve for impregnation, and then adding hydrobromic acid (40 wt%) dropwise under stirring for 3 hours; the mass volume of sodium bismuthate and hydrobromic acid is 1 g:10 mL; the mass ratio of the molecular sieve added in step (1) to the bismuth element in the bismuth salt solution is 100:3; centrifugation, washing the solid with water 3 times, and drying at 50°C for 6 hours to obtain BiOBr / titanium dioxide / molecular sieve;
[0071] (3) The BiOBr / titanium dioxide / molecular sieve and ammonium carbonate prepared above are uniformly dispersed in water, wherein the concentration of BiOBr / titanium dioxide / molecular sieve in water is 25 g / L; then a silver nitrate solution is added, wherein the mass ratio of the molecular sieve added in step (1) to the metal component in the active metal component precursor solution is 100:0.1; the molar ratio of ammonium carbonate to the active metal component precursor is 1:1, reacting at room temperature for 40 minutes, washing with water 3 times, drying at 60°C for 2 hours, and secondary calcining in an argon atmosphere at a temperature of 250°C for 1 hour to obtain the composite bismuth oxyhalide catalyst.
[0072] The composite bismuth oxyhalide catalyst prepared based on the above method includes a molecular sieve; titanium dioxide, bismuth oxybromide and an active metal component loaded on the molecular sieve; the mass ratio of titanium element in titanium dioxide to molecular sieve is 0.3:100; the mass ratio of bismuth element in bismuth oxybromide to molecular sieve is 2.5:100; and the mass ratio of active metal component to molecular sieve is 0.08:100.
[0073] Example 2
[0074] A method for preparing a composite bismuth oxyhalide catalyst comprises the following steps:
[0075] (1) Add titanium tetrachloride dropwise into ice water to prepare a titanium source solution (1.5 wt%); add molecular sieve (ZSM-5) into the titanium source solution for impregnation, wherein the mass ratio of molecular sieve to titanium element in the titanium source solution is 100:2.2; the impregnation temperature is 50°C and the impregnation time is 1.5 h; centrifugal separation is performed, the solid is washed with water 3 times, dried at 70°C for 2 hours, and in a mixed atmosphere of argon and hydrogen (the volume ratio of argon and hydrogen is 10:), the temperature is gradually increased from 70°C to 250°C for 15 minutes; the temperature is further increased to 300°C for 40 minutes; the temperature is further increased to 400°C for 25 minutes; the temperature gradient is 10°C / min to obtain titanium dioxide / molecular sieve;
[0076] (2) dissolving sodium bismuthate in a mixed solvent of water and alcohol (ethanol) (the volume ratio of water to alcohol is 1:3) to obtain a bismuth salt solution (5 wt%), then adding titanium dioxide / molecular sieve for impregnation, and then adding hydrobromic acid (42 wt%) dropwise under stirring for 4 hours; the mass volume of sodium bismuthate and hydrobromic acid is 1 g:12 mL; the mass ratio of the molecular sieve added in step (1) to the bismuth element in the bismuth salt solution is 100:4; centrifugation, washing the solid with water 3 times, and drying at 60°C for 5 hours to obtain BiOBr / titanium dioxide / molecular sieve;
[0077] (3) The BiOBr / titanium dioxide / molecular sieve and ammonium carbonate prepared above are uniformly dispersed in water, wherein the concentration of BiOBr / titanium dioxide / molecular sieve in water is 21 g / L; then a silver nitrate solution is added, wherein the mass ratio of the molecular sieve added in step (1) to the metal component in the active metal component precursor solution is 100:0.05; the molar ratio of ammonium carbonate to the active metal component precursor is 1:1.1, reacting at room temperature for 60 minutes, washing with water 3 times, drying at 50°C for 2 hours, calcining in an argon atmosphere, secondary calcination at a temperature of 250°C for 0.8 hours; and obtaining the composite bismuth oxyhalide catalyst.
[0078] The composite bismuth oxyhalide catalyst prepared based on the above method includes a molecular sieve; titanium dioxide, bismuth oxybromide and an active metal component loaded on the molecular sieve; the mass ratio of titanium element in titanium dioxide to molecular sieve is 0.2:100; the mass ratio of bismuth element in bismuth oxybromide to molecular sieve is 3:100; and the mass ratio of active metal component to molecular sieve is 0.05:100.
[0079] Example 3
[0080] A method for preparing a composite bismuth oxyhalide catalyst comprises the following steps:
[0081] (1) Loading of titanium dioxide: titanium tetrachloride was added dropwise into ice water to prepare a titanium source solution (0.5 wt%); molecular sieve (ZSM-5) was added to the titanium source solution for impregnation, and the mass ratio of molecular sieve to titanium element in the titanium source solution was 100:5; the impregnation temperature was 30°C and the impregnation time was 1.5 h; centrifugal separation was performed, the solid was washed with water 3 times, and dried at 60°C for 3 hours. In a mixed atmosphere of argon and hydrogen (the volume ratio of argon and hydrogen was 10:1.5), the temperature was gradually increased from 60°C to 250°C for 20 minutes; the temperature was further increased to 300°C for 30 minutes; the temperature was further increased to 400°C for 25 minutes; the temperature increase gradient was 5°C / min, and titanium dioxide / molecular sieve was obtained;
[0082] (2) Loading of bismuth oxybromide: Sodium bismuthate was dissolved in a mixed solvent of water and alcohol (ethanol) (the volume ratio of water to alcohol was 1:1.5) to obtain a bismuth salt solution (3 wt%), and then titanium dioxide / molecular sieve was added for impregnation, followed by dropwise addition of hydrobromic acid (40 wt%) under stirring for 3 h; the mass volume of sodium bismuthate and hydrobromic acid was 1 g:11 mL; the mass ratio of the molecular sieve added in step (1) to the bismuth element in the bismuth salt solution was 100:2; centrifugation was performed, the solid was washed with water 3 times, and dried at 50°C for 7 hours to obtain BiOBr / titanium dioxide / molecular sieve;
[0083] (3) Loading of active metal components: The BiOBr / titanium dioxide / molecular sieve and ammonium carbonate prepared above are uniformly dispersed in water, wherein the concentration of BiOBr / titanium dioxide / molecular sieve in water is 30 g / L; then a silver nitrate solution is added, wherein the mass ratio of the molecular sieve added in step (1) to the metal component in the active metal component precursor solution is 100:0.01; the molar ratio of ammonium carbonate to the active metal component precursor is 1:1, the reaction is carried out at room temperature for 30 minutes, the mixture is washed with water 3 times, dried at 50°C for 1 hour, the calcination atmosphere is argon, and a secondary calcination is carried out at a temperature of 250°C for 1 hour; and the composite bismuth oxyhalide catalyst is obtained.
[0084] The composite bismuth oxyhalide catalyst prepared based on the above method includes a molecular sieve; titanium dioxide, bismuth oxybromide and an active metal component loaded on the molecular sieve; the mass ratio of titanium element in titanium dioxide to molecular sieve is 0.8:100; the mass ratio of bismuth element in bismuth oxybromide to molecular sieve is 1:100; and the mass ratio of active metal component to molecular sieve is 0.01:100.
[0085] Example 4
[0086] The preparation method is basically the same as that of Example 1, except that pure silver nitrate solution is added into copper nitrate and silver nitrate solutions with equal metal moles, wherein the mass ratio of copper element in copper nitrate to silver element in silver nitrate in the solution is 0.5:1.
[0087] Example 5
[0088] The preparation method is basically the same as that of Example 1, except that pure silver nitrate solution is added into equal metal moles of palladium nitrate and silver nitrate solution, wherein the mass ratio of the Pd element in the palladium nitrate to the silver element in the silver nitrate in the solution is 0.4:1.
[0089] Example 6
[0090] The preparation method is basically the same as that of Example 1, except that pure silver nitrate solution is added to ruthenium nitrate and silver nitrate solutions in equal metal moles, wherein the mass ratio of ruthenium element in ruthenium nitrate to silver element in silver nitrate in the solution is 0.2:1.
[0091] Example 7
[0092] The preparation method is basically the same as that of Example 1, except that all molecular sieves are replaced by mordenite.
[0093] Example 8
[0094] The preparation method is basically the same as that of Example 1, except that all molecular sieves are replaced by ZSM-5.
[0095] Comparative Example 1
[0096] The same preparation method is adopted as Example 1, and the only difference is that the first calcination in this comparative example is carried out under a pure argon atmosphere.
[0097] Comparative Example 2
[0098] The same preparation method is used as in Example 1, except that the bismuth oxybromide loading step is not performed in this comparative example.
[0099] Comparative Example 3
[0100] The same preparation method is adopted as Example 1, the only difference being that the first calcination in this comparative example is carried out under a pure hydrogen atmosphere.
[0101] Comparative Example 4
[0102] The same preparation method is used as in Example 1, except that the titanium dioxide loading step is not performed in this comparative example.
[0103] Comparative Example 5
[0104] The same preparation method is adopted as Example 4, the only difference is that the mass ratio of copper and silver metal ions in this comparative example is 1:1.
[0105] Comparative Example 6
[0106] The same preparation method is adopted as Example 5, the only difference being that the mass ratio of the metal ions of Pd and silver in this comparative example is 1:1.
[0107] Comparative Example 7
[0108] The same preparation method is adopted as Example 6, the only difference being that the mass ratio of the metal ions of ruthenium and silver in this comparative example is 1:1.
[0109] Comparative Example 8
[0110] The same preparation method is used as in Example 5, with the only difference being that in this comparative example, the temperature is directly raised to 400 degrees for 90 minutes during the first calcination.
[0111] Comparative Example 9
[0112] The same preparation method is used as in Example 1, except that the Ag loading step is not performed in this comparative example.
[0113] The catalysts prepared in the above examples and comparative examples were subjected to photocatalytic activity evaluation using organic dye Rhodamine B. A 300W xenon lamp was used as the light source. The entire catalytic process was carried out in a glass beaker (cross-section 40 cm 2 , height 10cm). Weigh 1g sample and disperse it in 80mL Rhodamine B solution (25mg / L). Before illumination, magnetic stirring was carried out for 10h in dark conditions to reach adsorption / desorption equilibrium. 5mL samples were taken at 30min and 60min after illumination, and the absorbance was measured by UV-visible spectrophotometer. The specific results are shown in Table 1.
[0114] Table 1
[0115] sample Degradation rate of dye Rhodamine B in 30 minutes Degradation rate of dye Rhodamine B in 60 minutes Example 1 66% 94% Example 2 60% 91% Example 3 62% 92% Example 4 68% 96% Example 5 69% 96.5% Example 6 71% 97% Example 7 61% 90% Example 8 63% 93% Comparative Example 1 55% 87% Comparative Example 2 21% 32% Comparative Example 3 48% 75% Comparative Example 4 42% 68% Comparative Example 5 62% 91% Comparative Example 6 60% 89% Comparative Example 7 64% 92% Comparative Example 8 59% 90% Comparative Example 9 51% 85%
[0116] It can be seen from the results of the embodiments of the present invention and the comparative examples that the technical effect of the embodiments of the present invention is the best.
[0117] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0118] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0119] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0120] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
Claims
1. A method for preparing a composite bismuth oxyhalide catalyst, characterized in that: The following steps are involved: (1) adding titanium tetrachloride dropwise into ice water to prepare a titanium source solution; The molecular sieve is added into the titanium source solution for impregnation, the solid-liquid separation is performed, the solid is washed, dried, and calcined once to obtain titanium dioxide / molecular sieve; During the primary calcination, in a mixed atmosphere, the temperature is gradually increased from 60 to 80 degrees, and the temperature is increased to 250 degrees for heating for 10 to 30 minutes; the temperature is further increased to 300 degrees for heating for 25 to 40 minutes; the temperature is further increased to 400 degrees for heating for 25 to 35 minutes; wherein the temperature increase gradient is 5 to 15 degrees per minute; the mixed atmosphere is a mixed atmosphere of argon and hydrogen, and the volume ratio of argon to hydrogen is 10:0.8 to 2.3; (2) dissolving sodium bismuthate in a mixed solvent of water and alcohol to obtain a bismuth salt solution, then adding titanium dioxide / molecular sieve for impregnation, then dropping hydrobromic acid under stirring, separating the solid from the liquid, washing the solid, and drying to obtain BiOBr / titanium dioxide / molecular sieve; (3) BiOBr / titanium dioxide / molecular sieve and weak base are mixed uniformly in water, a solution containing an active metal component precursor is added to react, solid-liquid separation is performed, the solid is washed, dried, and secondary calcination is performed to obtain the composite bismuth oxyhalide catalyst; the secondary calcination temperature is 200-250 degrees Celsius, the calcination time is 0.5-1.5 hours, and the calcination atmosphere is argon atmosphere; The composite bismuth oxyhalide catalyst comprises a molecular sieve; Titanium dioxide, bismuth oxybromide and active metal components supported on a molecular sieve; The active metal component includes at least Ag.
2. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: In step (1), The concentration of titanium element in the titanium source solution is 0.5wt%-1.5wt%; The mass ratio of the molecular sieve to the titanium element in the titanium source solution is 100:2-5; The immersion temperature is 30-50°C and the immersion time is 1-1.5h; The method of solid-liquid separation is centrifugal separation; Wash 1-3 times; wash with water.
3. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: In step (2), The alcohol is selected from at least one of ethanol, methanol and propanol; The volume ratio of water to alcohol is 1:1.5-3; The concentration of bismuth element in the bismuth salt solution is 1wt%-5wt%; The mass ratio of the molecular sieve and the bismuth element in the bismuth salt solution in step (1) is 100:1.5-4; The concentration of hydrobromic acid is 30-50wt%; The mass volume of the sodium bismuthate and hydrobromic acid is 1g: 9-12mL; The method of solid-liquid separation is centrifugal separation; The dripping time is 2-4h; The number of washing times is 1-3 times; washing with water; The drying temperature is 40-60°C and the drying time is 5-7 hours.
4. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: In step (3), The weak base is selected from ammonium carbonate; The active metal component precursor is selected from at least one of copper nitrate, palladium nitrate, ruthenium nitrate and silver nitrate.
5. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: The following steps are involved: In step (3), The concentration of BiOBr / titanium dioxide / molecular sieve in water is 21-30 g / L; The mass ratio of the molecular sieve to the metal component in the active metal component precursor in step (1) is 100:0.01-0.15; The molar ratio of the weak base to the active metal component precursor is 1:1-1.
2.
6. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: In step (3), The reaction time is 30-60 minutes; The drying temperature is 50-60°C; the drying time is 1-2 hours.
7. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: The molecular sieve is selected from at least one of mordenite and ZSM-5; and / or, The active metal component further includes at least one of Pd, Ru, and Cu.
8. The method for preparing the composite bismuth oxyhalide catalyst according to claim 7, characterized in that: The silicon-aluminum molar ratio of mordenite molecular sieve is 10~50; the silicon-aluminum ratio of ZSM-5 molecular sieve is 20~40.
9. The method for preparing the composite bismuth oxyhalide catalyst according to claim 1, characterized in that: The mass ratio of titanium element to molecular sieve in titanium dioxide is 0.2~0.8:100; The mass ratio of bismuth element to molecular sieve in bismuth oxybromide is 1-3:100; The mass ratio of active metal component to molecular sieve is 0.01~0.08:100.
Citation Information
Patent Citations
Preparation method of visible-light response type attapulgite-BiOX-TiO2 compound photo-catalyst
CN103212428A